Review of NASA's Earth Science Enterprise Research Strategy for 2000-2010 (The National Academies Press, 2000)

Cooperation in the Energy Futures of China and the United States–Chinese Version (The National Academies Press, 2000)

Cooperation in the Energy Futures of China and the United States - National Research Council (The National Academies Press, 2000)
Today we recognize the importance of the pending transition in energy resource utilization in the coming century. Two major players in this transition will be two of the world's superpowers2014China and the United States. Cooperation in the Energy Futures of China and the United States focuses on collaborative opportunities to provide affordable, clean energy for economic growth and social development, to minimize future energy concerns, environmental threats to our global society, and the health and economic impacts on energy production and use.

Addressing the Nation's Changing Needs for Biomedical and Behavioral Scientists - National Research Council (The National Academies Press, 2000)
As biomedical and behavioral research progresses into new areas, the number of scientists active in various fields rises and falls, and the health needs of the U.S. population evolve, it is important to ensure that the preparation of future investigators reflects these changes. This book addresses these topics by considering questions such as the following: What is the current supply of biomedical and behavioral scientists? How is future demand for scientists likely to be affected by factors such as advances in research, trends in the employment of scientists, future research funding, and changes in health care delivery? What are the best ways to prepare prospective investigators to meet future needs in scientific research? In the course of addressing these questions, this volume examines the number of investigators trained every year, patterns of hiring by universities and industry, and the age of the scientific workforce in different fields, and makes recommendations for the number of scientists that should be trained in the years ahead. This book also considers the diversity of the research workforce and the importance of providing prospective scientists with the skills to successfully collaborate with investigators in related fields, and offers suggestions for how government and universities should structure their research training programs differently in the future.

The Spent-Fuel Standard for Disposition of Excess Weapon Plutonium: Application to Current DOE Options - National Academy of Sciences (The National Academies Press, 2000)

Forecasting Demand and Supply of Doctoral Scientists and Engineers: Report of a Workshop on Methodology - National Research Council (The National Academies Press, 2000)
This report is the summary of a workshop conducted by the National Research Council in order to learn from both forecast makers and forecast users about improvements that can be made in understanding the markets for doctoral scientists and engineers. The workshop commissioned papers examined (1) the history and problems with models of demand and supply for scientists and engineers, (2) objectives and approaches to forecasting models, (3) margins of adjustment that have been neglected in models, especially substitution and quality, (4) the presentation of uncertainty, and (5) whether these forecasts of supply and demand are worthwhile, given all their shortcomings. The focus of the report was to provide guidance to the NSF and to scholars in this area on how models and the forecasts derived from them might be improved, and what role NSF should play in their improvement. In addition, the report examined issues of reporting forecasts to policymakers.

Attracting Science and Mathematics Ph.D.s to Secondary School Education (The National Academies Press, 2000)
The National Research Council conducted a study to identify a set of incentives that state governments and local school districts can use to attract Ph.D. scientists and mathematicians to secondary school teaching positions. This project investigated the career ambitions of Ph.D.s in the physical and life sciences through focus groups and a national survey to determine the kinds of work conditions and compensation packages that would induce them to take positions teaching physics, chemistry, biology, and various electives in public high schools or positions developing secondary school science and mathematics curricula. The study conducted interviews with Ph.D.s who are already teaching in secondary schools to ascertain information from their experiences, with local school district administrators to assess what they are realistically willing to offer Ph.D. scientists to attract them, and with higher education administrators to explore programmatic changes they would need to institute to provide Ph.D.s with skills tailored to secondary school teaching. These investigations led to this report which describes the incentives local school districts could use in establishing pilot programs in this area.

Measuring the Science and Engineering Enterprise: Priorities for the Division of Science Resources Studies - National Research Council (The National Academies Press, 2000)
The science and engineering enterprise has continued to evolve, responding over the last decade to increased economic globalization, a post-cold war military, federal budget fluctuations, and structural changes in the way science and engineering are conducted and innovations are adopted. This report suggests ways to revise the data collection activities of the Science Resources Studies Division (SRS) of the National Science Foundation to better capture the current realities of R&D funding and S&E human resources. The report's recommendations would improve the relevance of the data on graduate education, the labor market for scientists and engineers, and the funding and conduct of research and development, and thus better meet the data needs of policymakers, managers, and researchers.